SOIL FERTILITY STATUS OF PADDY GROWING RED SOILS OF CENTRAL TELANGANA ZONE DISTRICTS OF TELANGANA STATE, INDIA - K. P. VANI; D. SRINIVASA CHARY, D. RAJASHEKHAR, A. MADHAVI, P. SURENDRA BABU, T RAMPRAKASH (The Journal of Research, PJTSAU, 2023)
Soil fertility evaluation of an area is an important aspect in context of sustainable agriculture production. The macronutrients regulate soil fertility and control crop growth and yields. In this inquiry, the Central Telangana Zone (CTZ) in the State of Telangana was chosen, and the availability of macronutrients and their relationship to physico-chemical characteristics in red soils were explored. Forty five red soil predominated mandals were chosen and 59 surface soil (0-15 cm) samples collected from red soil predominated mandals and analyzed for physico-chemical properties and available N, P and K status using standard laboratory procedures. The value of pH, electrical conductivity, and organic carbon was ranged from 6.65 to 7.78, 0.02 to 0.72 dS m-1 and 0.19 to 0.51% respectively. The available N, P2O5 and K2O was ranged from 50 to 314, 17 to 147 and 72 to 627 kg ha-1, respectively. The available nitrogen was in low, phosphorus and potassium contents were in high. Available micronutrients iron and zinc was ranged from 0.58 to 5.92 and 0.06 to 4.81 mg kg-1, respectively. Out of 59 collected soil samples, 97% were low in available nitrogen, 90% and 47% were high in available phosphorus and potassium respectively.